Strategic optimization of PV integrated fuel cell systems for energy surplus utilization in grid failure scenarios - Gulzar, Muhammad Majid; Naeem, Muhammad Muzammil; Shahid, Kamal; Naeem, Farwa Amna; Alqahtani, Mohammed; Khalid, Muhammad (Frontiers in Energy Research, 2024)
Effective energy management in grid-connected renewable energy systems is essential for achieving cost-efficiency and reliability. This work presents a versatile control technique to tackle power system difficulties in grid-connected and grid-failure modes. The concept employs a digital iterative approach to optimize the operation of a DC-DC converter, guaranteeing the attainment of maximum power output and stability. During a grid breakdown, the system injects carefully adjusted active power into the grid to ensure that voltage and current levels are maintained at appropriate levels, hence preventing overloading. The proposed strategy exhibits a 99% enhancement in system responsiveness and a 96% decrease in overshoot when compared to conventional methods, thus substantiating its efficacy in practical scenarios.